IMPROVING LEARNING THROUGH CASE STUDY COMPETITIONS: CHALLENGES FOR TEACHERS AND STUDENTS (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2017)
The main aim of this research paper is to identify the different perspectives of students and teachers from two SEE countries on the case learning method in local case study competitions. This research investigates the benefits and challenges of participating in case study competitions for students and mentors. Previous research is extended to include the teachers’ perspectives. Qualitative research has been conducted in Serbia and Croatia to obtain a better insight into the perspectives of all parties involved. Students are found to have difficulties with time management and identifying financial and sales implications of marketing strategies. Mentors, on the other hand, emphasize that students have difficulties with negotiation skills and identifying financial and sales implications of the marketing strategy recommended.Recommendations on how to improve learning through case study competitions are made. They should serve as guidelines for both teachers and students to help them to improve the learning process using marketing case studies. Keywords: Case-based learning, local case study competition, marketing case study, Croatia, Serbia